Parallel importation and compulsory licensing-impact on drug prices in Malaysia - Rodziah, Ahmad. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Trade-Related Aspects to Intellectual Property Rights (TRIPS) Aggrement provision on parallel importation and compulsory licensing had been major is discussed among World Trade Organization country members to promote acc to essential medicines in low-income country.